Epidemiological and Immunological Features of Influenza Viruses in Hospitalized Children with Influenza Illness in Hangzhou. (2nd January 2020) - Li, Wei; Liu, Li-Fang; Xu, Jia-Lu; Shang, Shi-Qiang
Abstract: Objectives: We evaluated the epidemiological features and various inflammatory markers in hospitalized children with influenza virus infection in China. Methods: The real-time RT-PCR assay was performed for detection and genotyping of influenza A and B virus. Th1/Th2 cytokines, WBC, and CRP were determined in influenza virus positive children. Results: H1N1 and Yamagata were the prevalent genotypes of influenza A and B virus in Hangzhou, respectively. IL-2, IL-10, and CRP were significantly increased and IFN-γ was decreased in children with severe Influenza A virus infection, and TNF-α and IFN-γ levels were found to be significantly lower in children with severe Influenza B virus infection. Conclusion: Increased IL-2, IL-10, and CRP with decreased IFN-γ may indicate a severe influenza A virus infection, and decreased TNF-α and IFN-γ may indicate a severe influenza B virus infection in children.